Kerma area product (KAP) and scatter measurements for intraoral X-ray machines using three different types of round collimation compared with rectangular beam limiter - Magill, Dennise (Dentomaxillofac Radiol, 2018)
OBJECTIVES: The objective of the study was to determine the radiation dose reduction achieved when rectangular collimation was used on various round collimators. In addition, we evaluated the tissue doses imparted to various head and neck organs. METHODS: To evaluate the variation in radiation output based on the variable geometric configurations, the kerma area product (KAP) was measured using a commercially available KAP-meter with an internal ion chamber capable of detecting both radiation dose (µGy) and the primary X-ray beam area. The KAP was measured using standard 20.4, 25.7, and 31.7 cm(2) round collimators with and without rectangular X-ray field restrictors. To evaluate the potential change in patient scatter radiation dose, an adult head phantom was loaded with thin strips of gafchromic film. A full mouth X-ray series was acquired with various geometric configurations. The films were quantified using a calibration factor to yield absorbed organ doses for the eyes, thyroid, and salivary glands. RESULTS: With the use of rectangular collimator, the KAP for a 31.7 cm(2) round collimator was reduced by up to 60% while the 20.4 cm(2) round collimator elicited a reduction from up to 40%. In the organ study, results of up to 81% reduction in scatter radiation dose were observed. CONCLUSIONS: Although, US FDA regulations allow a maximum beam size of 38.5 cm(2) on the patient skin, this study suggests that the use of rectangular collimators provide clinically relevant dose reduction for patients, even when using smaller round collimation, hence the use of rectangular collimation for all intraoral radiographic procedures is highly recommended.